Narasi Perempuan melalui Tato - Purnama, Nikita Devi; Putri, LG Saraswati (UI Scholars Hub, 2021)
This research examines how women voice their narratives through tattoos by studying the experiences of seven tattooed women. Using the in-depth interview method, this research presents the narratives of these tattooed women in relation to their tattoos. Such narratives seem to be strongly intertwined with their life stories. The body is a medium in which a person can place certain markers to achieve certain purposes. As Butler theorizes, what the body displays is not the real self, but only an appearance according to the assumed or chosen role. In addition, according to Cixous, tattooing can be considered as a form of writing and appropriation of expression for women who are far removed from traditional forms of language as a medium of communication which often serves patriarchic interests. As such, tattoos differ from symbols that outsiders can simply read. Women have their own process of choosing the permanent mode of writing on their bodies, and to understand that, we need to listen to the their narratives. When referring to the process and life story of women, tattoos also contain a narrative that is full of women's specific life experiences.